Pertanggungjawaban Para Pihak dalam Perjanjian Sewa Tempat Usaha di Magelang - Zahra, Afra; Silviana, Ana (Program Studi Magister Kenotariatan, Fakultas Hukum, Universitas Diponegoro, 2026)
ABSTRACTThis study examines the accountability of tenants in rental agreements for business premises at the